2021
DOI: 10.1093/jtm/taab024
|View full text |Cite
|
Sign up to set email alerts
|

‘Blue toes’ following vaccination with the BNT162b2 mRNA COVID-19 vaccine

Abstract: Highlights: COVID toes can be encountered in young individuals during acute COVID-19 infection while it results from the direct action of Spike protein on vessels. We report the case of COVID toes during the French campaign of vaccination that occurred 4 days after the vaccination with the Pfizer-BioNTech mRNA vaccine against COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…[1][2][3][4][5][6] It has been postulated that this apparent contradiction could be explained as virus-induced interferonopathy associated with a strong activation of innate immune system and fast clearance of antibodies. 7,8 Recently, Davido et al 9 reported a similar case in a 41-yearold woman developing 'blue toes' after BNT162b2 mRNA COVID-19 vaccine. Differently from our case, the patient developed CLL 4 days after the first dose of the vaccine, leading to avoid the second dose for safety reasons.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6] It has been postulated that this apparent contradiction could be explained as virus-induced interferonopathy associated with a strong activation of innate immune system and fast clearance of antibodies. 7,8 Recently, Davido et al 9 reported a similar case in a 41-yearold woman developing 'blue toes' after BNT162b2 mRNA COVID-19 vaccine. Differently from our case, the patient developed CLL 4 days after the first dose of the vaccine, leading to avoid the second dose for safety reasons.…”
mentioning
confidence: 97%
“…The chilblains-like lesions suggest that she had an antibody response from either 1 vaccine dose or a previous PCR-negative COVID-19 infection. 4 The understanding of the SARS-CoV-2 virus and the vaccines against it is a rapidly evolving landscape. 5 The Journal of Rheumatology 2021;xx:xxxx doi:10.3899/jrheum.210226 First Release July 1 2021…”
mentioning
confidence: 99%
“…We will take into account confounding factors [17][18][19][20][21][22], previously proposed approaches [22][23][24] and will also review reports from social media and clinical case studies. Literature reviews of long-term and unusual side effects of COVID-19 vaccines will be performed continuously, including evaluation of dynamically evolving Adverse Events of Special Interest (AESI) and establishing background rates for these AESI [25][26][27][28][29][30][31][32][33][34][35][36]. We will also analyze breakthrough infections and efficacy of COVID-19 vaccines in different communities and populations [37][38][39][40][41][42][43][44].…”
Section: Potential Benefitsmentioning
confidence: 99%